The methylation status of TNF-α and SOCS3 promoters and the regulation of these gene expressions in patients with Behçet's disease. (3rd July 2020) - Aziz, Shiva Gholizadeh-Ghaleh; Aziz, Sara Gholizadeh-Ghaleh; Khabbazi, Alireza; Alipour, Shahriar
Abstract: Introduction: The aim of this study was to evaluate the methylation status of TNF-α and SOCS3 promoters in patients with BD and compare them with a healthy group. Method: This was a case–control study, in which 47 subjects with BD and 61 individuals as the control participated. Blood samples were collected from all the participants. Then, PBMCs were isolated using the Ficoll method and methylation of considered sites was investigated using the qMS-PCR technique after DNA extraction by the rapid genomic DNA extraction method and its analysis with Nano-drop. Results: The methylation and expression of TNF-α showed that the methylation level significantly declined in the patient in comparison with the healthy ( p  < 0.05). Moreover, the results on the mean expression showed that it significantly increased in the patient group, as compared with the healthy group ( p  < 0.05). In addition, the expression of the SOCS3 gene was not significantly different between the patients and healthy subjects while the level of SOCS3 methylation was significantly higher in the patient group than that in the healthy group ( p  < 0.05). Discussion: The present study revealed that the gene expression of TNF-alpha increased in BD patients, suggesting that TNF-alpha likely has a role in the pathogenesis of BD.